METHODS OF EVALUATING EFFICIENCY IN INDUSTRIAL ENTERPRISES - Yuldasheva Kamola Miralievna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
The article discusses the management of innovative processes at an enterprise, methods for assessing the innovative activity of an industrial enterprise, as well as a methodology for assessing the effectiveness of innovative processes.